A life-cycle integrated model for product eco-design in the conceptual design phase. (20th August 2022) - Kong, Lin; Wang, Liming; Li, Fangyi; Tian, Guangdong; Li, Jianfeng; Cai, Zekang; Zhou, Jiaxuan; Fu, Yan
Abstract: Eco-design that addresses the consumption of resources and energy, as well as pollution emissions from a product life-cycle perspective, is an effective way to solve environmental problems. However, the optimal eco-design solution is hardly generated in the conceptual design stage due to the complex association of the life cycle design information. To this end, this paper proposes a new eco-design model based on a life cycle integrated framework to effectively manage life cycle information in the conceptual design phase. In this work, (1) The life cycle-oriented model is proposed to integrate the product design information in terms of a systematic association mechanism between function, structure, material and process to construct the design space. (2) A life cycle design scenario-based similarity matching method is developed to support the environmental impact assessment of design options in the design space. (3) A hope tree-based heuristic search algorithm with the principle of minimizing environmental impact is proposed to efficiently obtain the eco-design solution. An application for eco-design of the lift equipment is given to demonstrate the capability of the proposed method. The results show that the environmental impact of the generated eco-design solution is improved by 19.48%, and the material and use stage has the highest environmental impact which accounts for 39.59% and 47.74% respectively. This work provides a targeted method for guiding designers to implement eco-design in the conceptual design phase through the life cycle. Graphical abstract: Image 1 Highlights: An integrated life cycle model is proposed to express the design information of function, structure, material and process. A scenario-based similarity matching method is proposed to acquire the LCI for the design options. Hope tree-based algorithm is used to efficiently obtain the optimal eco-design solution.